2007
DOI: 10.2320/matertrans.48.234
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Frequency of Electromagnetic Vibrations on Vibrational Motion in Fe-Co-B-Si-Nb Bulk Metallic Glasses

Abstract: The method for producing Fe-Co-B-Si-Nb bulk metallic glasses using electromagnetic vibrations is effective in forming the metallic glass phase. The purpose of this study was to investigate the effects of the frequency of electromagnetic vibrations on the vibrational motion in Fe-Co-B-Si-Nb bulk metallic glasses. The amplitudes of the electromagnetic vibrations at 5 kHz were calculated to be on the order of micrometers, but those at higher frequencies were on the order of nanometers. It was found that the nanom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…We showed that as the O-U-O bond angle becomes stiffer, water exchange dynamics become slower. It has been observed that large magnetic fields perturb the vibrational frequencies of molecules [66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84] and this could result in a distortion of the exchange dynamics measured with NMR. The third explanation is that the models used in the simulations are simply not sophisticated enough to capture the dynamical exchange process between water and UO 2 2+ and need to be improved.…”
Section: +mentioning
confidence: 99%
“…We showed that as the O-U-O bond angle becomes stiffer, water exchange dynamics become slower. It has been observed that large magnetic fields perturb the vibrational frequencies of molecules [66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84] and this could result in a distortion of the exchange dynamics measured with NMR. The third explanation is that the models used in the simulations are simply not sophisticated enough to capture the dynamical exchange process between water and UO 2 2+ and need to be improved.…”
Section: +mentioning
confidence: 99%
“…This result is the same as the result of XRD. It is considered that heterogeneous crystalline nuclei exist in the liquid region when heat treatment temperature is close to the solidus temperature [16][17][18][19][20][21][22][23][24]. Thus, it is presumed that heterogeneous crystalline nuclei related to unknown crystalline phase decrease the glass forming ability for the samples heat treated at low temperatures.…”
Section: Thermec 2013mentioning
confidence: 99%
“…The displacement of the sample can be derived from two equations. [18] The Mg-based alloys with a diameter of 4 mm were experimented at a magnetic density of 10 T, a sample length of 10 mm, an alternating electric current of 20 A, and a weight of 0.4 g. Thus, the amplitude of the vibrational motion was calculated from two equations. The effect of the frequency of the electromagnetic vibrations on the calculated amplitude of the vibrational motion is shown in Table I.…”
Section: Figures 4(b) and (C) Show Magnified Micrographs Of The Left mentioning
confidence: 99%
“…It was suggested that this phenomenon is the reason electromagnetic vibrations decrease the number of crystal nuclei, because the clusters of crystals in the liquid state, which have lower electric resistance than the liquid metal, vibrate vigorously and disappear. [18] If the clusters that become crystal nuclei move by Lorentz force in the liquid metal, a direct electric current added to an alternating electric current for the electromagnetic vibrations is considered to shift the crystal particles in the direction of Lorentz force by a direct electric current.…”
Section: Introductionmentioning
confidence: 99%